Dermoscopy as an auxiliary method in the diagnosis of social wasp (Hymenoptera, Vespidae) stings - Luiz Gustavo Martins da Silva; Fred Bernardes Filho; Maria Victoria Quaresma; Elaine de Souza Pinto Leite; Andresa de Oliveira Marteloso; Natalia Ferreira Saldanha; Grabriela Goncalves Brum (Sociedade Brasileira de Dermatologia, 2014)
We describe the case of a 32-year-old male patient that sought medical treatment complaining of severe pain in his second and third right-hand fingers. The symptoms had started two hours before. The hypotheses of spider bite, scorpion or insect sting and injury caused by a foreign body were considered in the differential diagnoses. On dermoscopy, two foreign bodies were identified on his skin. After extraction, we concluded that they were wasp stingers.